Modern possibilities of antisecretory therapy in children. - T. V. Yaroshevskaya; N. B. Sapa; N. N. Kramarenko; S. P. Degtyar (Medičnì Perspektivi, 2015)
The article deals with the problem of antisecretory therapy in children with erosive gastric and duodenal lesions usingproton pump inhibitors. Taking into account low potential of side effects and drug interactions, pantoprazole was used for antisecretory therapy. Administration of preparation in two doses, one of which is in the form of intravenous infusion, from the first day of patients’ hospital stay led to the rapid relief or significant reduction of pain. In 86% of patients pain was completely controlled by day 7 of hospital stay. More than 90% of patients during therapy showed improvement of appetite and general well-being, reduction of dyspeptic symptoms (nausea, vomiting, belching). The proposed scheme of pantoprazole administration showed high efficacy and safety in chronic erosive gastroduodenitis therapy in children with severe pain.